Marital violence and women's employment and property status: evidence from North Indian villages - Manasi Bhattacharya; Arjun S. Bedi; Amrita Chhachhi (Institute for the Study of Labor (IZA), 2009)
Dominant development policy approaches recommend women's employment on the grounds that it facilitates their empowerment, which in turn is believed to be instrumental in enhancing women's well-being. However, empirical work on the relationship between women's employment status and their well-being as measured by freedom from marital violence yields an ambiguous picture. Motivated by this ambiguity, this paper draws on testimonies of men and women and data gathered from rural Uttar Pradesh, to examine the effect of women's employment and asset status as measured by their participation in paid work and their ownership of property, respectively, on spousal violence. Unlike the existing literature, we treat women's work status and violence as simultaneously determined and find that women's engagement in paid work and ownership of property, are associated with sharp reductions in marital violence.
urn:nbn:de:101:1-2009092819
Keywords: J12; J15; J16; 330; Domestic violence; employment status; property ownership; India; Gewalt; Ehe; Frauenpolitik; Frauenerwerbstätigkeit; Vermögensbildung; Indien